The advancements and use of technological strategies in performance analysis of soccer: an update - Pathmanathan Suppiah; Mohamad Razali Abdullah; Rabiu Muazu Musa; Norlaila Azura Kosni; Ahmad Bisyri Husin Musawi Maliki (2016)
Performance analysis in the game of soccer involves the collections of series of data based on relevant performance indicators on player’s performance to aid accelerate his development. The development of technological devices in performance analysis of soccer began from manual notation system to different sort of devices which ranges from simple to complex each having its own advantages and shortcomings. The purpose of this paper is to review the technological advancement in the performance analysis of soccer. Three significant improvements were discussed highlighting the contribution as well as the limitation of each system in the performance analysis of the game. Hand notational systems, tablet application systems, as well as computerized video analysis systems, were deliberated. Although each of the system used has its own contribution in the provision of feedback to improve performance, computerized video analysis system is considered to be the best in providing information for assisting the coach to improve both individual and team performances.